Development of Test Instruments to Measure Middle School Students' Creative Thinking Ability - Sahira, Perisha Elsa; Panggabean, Ellis Mardiana (Lembaga Riset Mutiara Akbar, 2022)
The development of creative thinking skills really needs to be done because this ability is one of the abilities that the world of work wants. Mathematics learning needs to be designed so that it has the potential to develop students' creative thinking. The observation results show that teachers still pay little attention to students' creative thinking skills. Creative thinking ability tests have been compiled and validated by the validator. Based on the identification and definition of the problem that has been simplified, the formulation of the problem in this study can be formulated, namely how is the test instrument for measuring the creative thinking abilities of junior high school students. The purpose of this study was to develop a test instrument that measures the creative thinking abilities of junior high school students. Based on the data obtained, the average validation result by experts is 3.36. and 84%. So, it can be concluded that the development of a test instrument to measure creative thinking skills is feasible to use